Hair matters: The psychoanalytical significance of the virtual absence of hair in the Book of Job in an African context - Zwan, Pieter van der (HTS teologiese studies, 2022)
Compared with other biblical books that are named after its main protagonist, Job mentions many (at least 72) body parts. Yet hair is explicitly referred to only once, even when it plays a relatively significant role in other books in the Hebrew Bible. This virtual absence of hair in the book can at first glance be explained by the shaving of Job’s ‘head’ as early as 1:20, using a different verb, גזז, from the one in Leviticus 13:33 and 14:8.9, גלח, where the context is that of צָרָעַת, wrongly translated as ‘leprosy’, but probably referring to the same skin problem from which Job is suffering. This connection to the skin is important, because the two body parts seem to be almost mutually exclusive, as also suggested by 1:21 immediately after the aforementioned shaving, where Job considers himself to be essentially עָרֹם [naked]. This means that hair has, amongst other functions, also a clothing-like role in the book of Job. Three questions will hence be explored: how ‘absence’ is to be psychoanalytically interpreted and more specifically, what consequences all of this has on the virtual absence of hair in the Book of Job and, finally, what relevance this absence has for the South African context.Contribution: Applying a psychoanalytical perspective to both the body and to absence, the biblical text is contextualised on a broader horizon than what the purely historical-critical approach can render. The additional African context widens the relevance of the ancient book even further.